L' exil à Londres jusqu'à la dissolution de la Ligue communiste, 1850-1853 - Marx, Karl; Engels, Friedrich (Paris : Alfred Costes, 1948)
Bibliotheek Camille Huysmans
Frans
Monografie
Keywords: Marx, Karl; Engels, Friedrich